Description of the female of Anasillus crinitus Marinoni & Martins 1978 (Coleoptera: Lamiinae: Acanthoderini) and new distribution records of longhorned beetles for Colombia - Taboada-Verona, Carlos; Botero, Juan Pablo (Zootaxa, 2019)
Marinoni & Martins (1978) proposed Anasillus for a single species, A. crinitus Marinoni & Martins, 1978, based on a single male specimen from Peru, and until now, the female remained unknown. Herein, the female of this species is described and illustrated for the first time, and its geographical distribution is expanded to Colombia. Additionally, the geographical distribution of seven species of Cerambycidae is expanded to Colombia: Coleoxestia vittata (Thomson, 1861); Sphallenopsis pilosovittata (Bates, 1872); Aneflus (Protaneflus) minutivestis Chemsak & Linsley, 1963; Mallocera amazonica Bates, 1870; Compsibidion charile (Bates, 1870); Alcidion sulphurifer (White, 1855); and Acanthoderes (Acanthoderes) ariasi Chemsak & Hovore, 2002.